Gel-Based Approaches to Vegan Leather: Opportunities and Challenges in Mimicking Leather Properties - Soon Mo Choi; Do Hyun Lee; Sun Mi Zo; Ankur Sood; Sung Soo Han (Gels)
Recently, increased global awareness of environmental sustainability and ethical consumerism has amplified the demand for sustainable alternatives to animal-derived leather. Traditional leather manufacturing faces significant ethical and ecological challenges, including greenhouse gas emissions, excessive water consumption, deforestation, and toxic chemical usage. Vegan leather has emerged as a promising solution, predominantly fabricated from petroleum-based synthetic materials such as polyurethane (PU) and polyvinyl chloride (PVC). However, these materials have sustainability limitations due to their non-biodegradability and associated environmental burdens. To overcome these issues, this review critically explores the feasibility of developing vegan leather using gel-based materials derived from natural and synthetic polymers. These materials offer precise structural controllability, excellent biodegradability, and the potential for significantly improved mechanical performance through hybridization and nanocomposite strategies. Despite their promising attributes, gel-based materials face significant limitations, including insufficient tensile strength, poor abrasion resistance, susceptibility to swelling, limited long-term stability, and challenges in scaling up for industrial production. This paper outlines the structural and physical properties required for viable leather substitutes, reviews opportunities provided by gel-based materials, addresses associated technical challenges, and proposes comprehensive strategies for enhancing mechanical properties and developing sustainable, eco-friendly production processes. Future research directions emphasize hybrid composite development, nanoparticle integration, circular manufacturing processes, and multi-disciplinary collaboration to establish gel-based vegan leather as a viable, sustainable, and market-competitive alternative to conventional animal leather.